PHARMACOKINETICS AND BIOAVAILABILITY OF ORTHOSIPHON STAMINEUS ETHANOLIC EXTRACT AND ITS-NANO LIPOSOMES IN SPRAGUE-DAWLEY RATS - Shafaei, Armaghan; Saeed, Mohammed Ali Ahmed; Aisha, Abdalrahim F. A.; Ismail, Zhari (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study aimed to perform pharmacokinetic profile of rosmarinic acid (RA), sinensitin (SIN), eupatorin (EUP) and 3΄-hydroxy-5,6,7,4΄-tetramethoxyflavone (TMF) in Orthosiphon stamineus ethanolic extract (OS-E) and its nanoliposomes (OS-EL) after oral and intravenous administration in Sprague-Dawley rat's plasma by developing and validating a high-performance liquid chromatography (HPLC) method with ultraviolet (UV) detection. Methods: An isocratic elution program consisting of methanol: tetrahydrofuran: water (0.1% H3PO4) mixture in the volume ratio 55: 5: 40 on Nucleosil C18 column (250 × 4.6 mm internal diameter × 5 µm particles size) was applied. The current study followed a two-ways crossover study design. OS-E and OS-EL were administered orally at 1000 and 500 mg/kg, respectively. They were also administered intravenously at 250 mg/kg via the tail vein. Results: The HPLC-UV method was successfully developed and validated for simultaneous determination of major chemical constituent from OS-E and OS-EL in rat's plasma. The method recorded the mean recoveries from extraction were between 91.39 and 100.32%. With regards to the intravenous administration of OS-EL, all four marker compounds appeared to be poorly distributed and cleared slowly from the body compared to OS-E. Whilst in oral administration of OS-EL, the bioavailability of all marker compounds were higher than OS-E due to higher solubility of encapsulation in phospholipids. Conclusion: The higher solubility and bioavailability of OS-EL may contribute to encapsulation in phospholipids.